Resveratrol Decreases Noise‐Induced Cyclooxygenase‐2 Expression in the Rat Cochlea. Issue 5 (4th February 2013) - Seidman, Michael D.; Tang, Wenxue; Bai, Venkatesh Uma; Ahmad, Nadir; Jiang, Hao; Media, Joseph; Patel, Nimisha; Rubin, Cory J.; Standring, Robert T.
Abstract : Objective: Our previous studies have demonstrated the efficacy of resveratrol, a grape constituent noted for its antioxidant and anti‐inflammatory properties, in reducing temporary threshold shifts and decreasing cochlear hair cell damage following noise exposure. This study was designed to identify the potential protective mechanism of resveratrol by measuring its effect on cyclooxygenase‐2 (COX‐2) protein expression and reactive oxygen species (ROS) formation following noise exposure. Study Design: Controlled animal intervention study. Setting: Otology Laboratory, Henry Ford Health System. Subjects and Methods: Twenty‐two healthy male Fischer 344 rats (2‐3 months old) were exposed to acoustic trauma of variable duration with or without intervention. An additional 20 healthy male rats were used to study COX‐2 expression at different time points during and following treatment of 24 hours of noise exposure. Cochlear harvest was performed at various time intervals for measurement of COX‐2 protein expression via Western blot analysis and immunostaining. Peripheral blood was also obtained for ROS analysis using flow cytometry. Results: Acoustic trauma exposure resulted in a progressive up‐regulation of COX‐2 protein expression, commencing at 8 hours and peaking at 32 hours. Similarly, ROS production increased after noise exposure. However, treatment with resveratrol reduced noise‐induced COX‐2 expression as well as ROS formation in the blood as compared with the controls. Conclusion: COX‐2 levels are induced dramatically following noise exposure. This increased expression may be a potential mechanism of noise‐induced hearing loss (NIHL) and a possible mechanism of resveratrol's ability to mitigate NIHL by its ability to reduce COX‐2 expression.